Комори українського Полісся та Наддніпрянщини - Верговська М. (Народна творчість та етнографія, 2008)
Genetic evolution of komora (pantry) as the bearer of preservation one can trace in two aspects: forming of functional adaptation and forming of the specific type of the construction. Initially it was a household pit, which later became a separate construction and gained branched and functional forms.